Examination of gram positive bacteria on salt-pack cured hides - (:unkn) unknown (My University, 2011)
Salt-pack curing method has been a widely used hide preservation method in worldwide. In order to evaluate the efficiency of the salt-pack curing process on the hides. Grampositive bacteria on the hides were characterized and their proteolytic and lipolytic activities were examined. Salt-pack cured hides examined were collected from different tanneries in Leather Organized Tannery Region, Tuzla-Istanbul, Turkiye and 40% of the hides were imported from abroad. A total of 396 Gram-positive bacteria comprising from 12 different genera (Aerococcus, Aneurinibacillus, Bacillus, Brevibacillus, Enterococcus, Geobacillus, Kocuira, Lactococcus, Paenibacillus, Streptococcus, Staphylococcus and Virgibacillus) and 47 bacterial species were isolated and identified from the hides. The total numbers of proteolytic, lipolytic and both proteolytic and lipolytic isolates on the hides were found as 278,274 and 226, respectively. The most common Gram-positive genera on the salted hides were Staphylococcus (115 isolates). Bacillus (111 isolates) and Enterococcus (75 isolates). Bacillus and Staphylococcus isolates showed both proteolytic and lipolytic activities in the highest number on the hides. The results verified that the saltpack curing method was not efficient in preserving the raw cattle hides. As a conclusion, since the salt-pack curing method were not applied adequately, a wide variety of Gram- positive bacterial species were isolated from the salt-pack cured hides. Therefore, the salt-pack curing method should be modified to inactivate Gram-positive bacteria found on the salt-pack cured hide samples.